Atrial Fibrillation in Older People: Concepts and Controversies - Zathar, Zafraan; Karunatilleke, Anne; Fawzy, Ameenathul M.; Lip, Gregory Y. H. (Frontiers in Medicine, 2019)
Atrial fibrillation (AF) is the commonest cardiac rhythm disturbance affecting the general population. Although asymptomatic in many patients, AF increases the risk of ischaemic strokes, hospitalisations and death. Indeed, As age is an independent risk factor for AF, the global burden of this condition is expected to increase with the ageing population. The management and treatment of this common arrhythmia in the elderly has been challenging, as they are a heterogenous group of individuals complicated by the presence of functional and social factors that contribute to their vulnerability, in addition to multimorbidity and polypharmacy. In this review, we aim to provide an update on the concepts and controversies in managing AF in older individuals, with respect to the current practice and existing literature.